Evaluation of pharmacokinetics and blood-brain barrier permeability of mitragynine using in vivo microdialysis technique - Kong, W.M.; Mohamed, Z.; Alshawsh, M.A.; Chik, Z. (Elsevier, 2017)
A microdialysis system coupled with a sensitive ultra-fast liquid chromatography–mass spectrometry (UFLC-MS) method was developed for the pharmacokinetic analysis of mitragynine in rat blood and striatum. Mitragynine is an active alkaloid of Mitragyna speciosa and has been proposed to be used for opioid withdrawal therapy. In this study, chromatographic separation was performed in a gradient elution mode with 0.1% formic acid and acetonitrile on a Zorbax Eclipse C18 column. The mass spectrometric (MS) analysis was carried out in a positive electrospray mode and mitragynine ion (m/z 399.2) was monitored in extracted ion chromatography. A good linearity range was obtained from 10-1000 ng/mL with acceptable accuracy and precision parameters. The microdialysate was collected simultaneously from the striatum and the right jugular vein using microdialysis probes. After a single intravenous administration of 10 mg/kg mitragynine, mitragynine showed a two-compartmental drug elimination pattern with half-life (T1/2) of approximately 13 h. The percent of AUCbrain/AUCplasma of mitragynine was calculated and shown to be 65.8 ± 4.5%. The results indicated that mitragynine could be a suitable molecule to develop into an opioid replacement drug based on its ideal pharmacokinetic properties, namely, small molecular size, lipophilic in nature and with excellent blood–brain barrier (BBB) permeability.